INFORMATION OVERSTIMULATION, STRESS, AND ACADEMIC BURNOUT: AN ONTOLOGICAL ANALYSIS OF SCHOOL LEARNING PRACTICES - Nurmala Dewi Qadarsih; Purni Munah Hartuti; Henny Suharyati (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
The phenomenon of digitalization of education has resulted in a significant transformation in learning practices in schools, especially through the rapid flow of information received by students. This condition causes symptoms of information overstimulation which has the potential to cause academic stress and learning fatigue. This research aims to examine the ontological essence of information overstimulation, stress, and academic fatigue in the context of learning practices in schools. This research uses a qualitative approach with a critical review of the literature on educational philosophy, educational psychology, and modern learning theory. The findings of this research indicate that, ontologically, information overstimulation is an objective reality that arises from an imbalance between students' cognitive capacities and the demands of an information-rich learning environment. Stress and burnout in learning are understood as psycho-educational entities that are not only individual but also socially and systemically constructive in the educational ecosystem. These findings underscore the need for a reorganization of modern educational practices, taking into account the ontological boundaries of learners as holistic educational subjects. This research implies the importance of learning design that focuses on cognitive balance, psychological well-being, and meaningfulness of learning.